Effect of Relationship Between β-Catenin and Extracellular Matrix on Progression of Oral Epithelial Dysplasia to Oral Squamous Cell Carcinoma - Abdel Ghani, Seham Ahmed (2025)
This study aimed to explore roles of β-catenin, collagen&elastic fibers in progression of Oral Epithelial Dysplasia (OED) to oral squamous cell carcinoma (OSCC). Sixty paraffin wax blocks of oral mucosa were divided into: control (Group I), mild OED (Group II), severe OED (Group III), well differentiated SCC (Group IV), moderately differentiated SCC (Group V), poorly differentiated SCC (Group VI). The sections underwent staining using hematoxylin and eosin, histochemical stains and β-catenin immunostaining.  Group I revealed normal gingival tissue. Group II showed some basal and prickle cells with pleomorphic nuclei. Group III illustrated poorly demarcated cell membrane. Group IV showed keratinized epithelial islands. Group V was devoid of keratin pearls. Group VI showed dispersed epithelial cells. β-catenin-immunoreactivity was; strong membranous in Group I, moderate membranous, cytoplasmic and nuclear in Groups II&III, moderate nuclear and cytoplasmic in Group IV but strong in Groups V&VI. Collagen fibers were closely packed in Groups I&II, loosely packed in Groups III&IV, dispersed in Groups V&VI. Elastic fibers in Group I were apparently few & thin, abundant in Group II, numerous in Group III, short in Groups IV&V and thick in Group VI. β-catenin and elastic fibers were upregulated meanwhile collagen formation was downregulated towards progression from mild OED to poorly differentiated SCC.